Aqueous hydrotropes: An efficient and reusable catalyst for the synthesis of 3-carboxy-coumarin motifs at room temperature - Baviskar, Pavan Devidas; Kale , Arun Dinkar; Mahire , Vilas Nana; Gosavi, Swati Dnyaneshwarpuri; Dalal, Dipak Sharadrao; Mahulikar, Pramod Pandurang (European Journal of Chemistry, 2024)
The coumarin moiety plays an important role in the large number of natural products possessing different kinds of biological diversity. Coumarin carboxylic acids show a wide range of biological activities in the pharmaceutical and agricultural fields. Knoevenagel condensation is one of the important reaction pathways for synthesizing coumarin derivatives, and many methodologies have been developed to synthesize this class of compounds. A more environmentally friendly method of synthesizing 3-carboxy coumarins has been successfully carried out using 50% aqueous NaPTS hydrotropes at room temperature, along with various substituted 2-hydroxy benzaldehydes and Meldrum’s acid. This process involves Knoevenagel condensation followed by intramolecular cyclization, providing better product yields (78-95%).